At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

A table of values for f, g, f prime, and g prime are given below. Let p(x) = f(5x) + f(g(x)) + g * (x) ^ 2 your work Using differentiation rules, find a general expression for p^ prime (x) .

A Table Of Values For F G F Prime And G Prime Are Given Below Let Px F5x Fgx G X 2 Your Work Using Differentiation Rules Find A General Expression For P Prime X class=

Sagot :

Applying derivative rules, it is found that p'(1) = 19.

The function given is:

[tex]p(x) = f(5x) + f(g(x)) + g(x)^2[/tex]

The derivative is the sum of derivatives, thus:

[tex]p^{\prime}(x) = [f(5x)]^{\prime} + [f(g(x))]^{\prime} + [g(x)^2]^{\prime}[/tex]

Applying the shifting rule:

[tex][f(5x)]^{\prime} = 5f^{\prime}(x)[/tex]

Applying the chain rule:

[tex][f(g(x))]^{\prime} = f^{\prime}(g(x))g^{\prime}(x)[/tex]

Applying the power of x, along with the chain rule:

[tex][g(x)^2]^{\prime} = 2g(x)g^{\prime}(x)[/tex]

Thus:

[tex]p^{\prime}(x) = 5f^{\prime}(x) + f^{\prime}(g(x))g^{\prime}(x) + 2g(x)g^{\prime}(x)[/tex]

At x = 1:

[tex]p^{\prime}(1) = 5f^{\prime}(1) + f^{\prime}(g(1))g^{\prime}(1) + 2g(1)g^{\prime}(1)[/tex]

From the table:

[tex]p^{\prime}(1) = 5(-1) + 6f^{\prime}(0)[/tex]

[tex]p^{\prime}(1) = -5 + 6(4)[/tex]

[tex]p^{\prime}(1) = 19[/tex]

A similar problem is given at https://brainly.com/question/22257133